2015
DOI: 10.4040/jkan.2015.45.4.513
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Experiences of the Death of Patients in Geriatric Hospitals

Abstract: Purpose: The purpose of this study was to identify and understand nurses' experiences of the death of patients in geriatric hospitals. Methods: Van Manen's hermeneutic phenomenological analysis was applied in the interpretation of experiential descriptions of seven nurses who had experienced the death of patients in a geriatric hospital. Results: The essential subjects derived from the experience of the nurses on the death of patients in a geriatric hospital are covered in the following 7 themes. 'Placed in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
2
0
4
Order By: Relevance
“…Researchers have identified that excessive exposure to the death of patients leads to compassion fatigue for nurses [ 3 ]. Additionally, when nurses actually experience patients’ deaths, some negative feelings including guilt, depression, frustration, sadness, incompetence, helplessness and distress come over them [ 4 – 7 ]. Hiding feelings and working continuously are common coping strategies they choose, as they are worried that showing their feelings may influence other’s perceptions of their professionalism [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have identified that excessive exposure to the death of patients leads to compassion fatigue for nurses [ 3 ]. Additionally, when nurses actually experience patients’ deaths, some negative feelings including guilt, depression, frustration, sadness, incompetence, helplessness and distress come over them [ 4 – 7 ]. Hiding feelings and working continuously are common coping strategies they choose, as they are worried that showing their feelings may influence other’s perceptions of their professionalism [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…③ 하나의 이상적인 애도 방식만을 따르진 않는다 (15). ④ 자신과 가족을 생각하며 자신의 삶을 반추하는 것 이다 (6,10). ⑤ 인간 삶과 죽음을 성찰하고 인간 존엄을 실천하는 것이다 (7,31,32).…”
Section: ) 잠정적 기준 목록unclassified
“…③ 의연하게 바라보기 (7,9,21,28,30) ④ 인간 존엄 실천하기 (7,10,21,31,32) 본 연구를 통해 확인된 속성을 바탕으로 간호사의 환 자죽음 수용이란 '환자죽음을 경험한 간호사가 애도를 통해 도달하는 단계로써 자신의 삶을 반추해서 삶과 죽 음에 대한 통찰력을 얻고, 환자죽음을 의연하게 바라보 며 인간 존엄을 간호 현장에서 실천하는 것'으로 정의 하였다.…”
Section: 30-32)unclassified
See 2 more Smart Citations